Bibliometric analysis of the scientific production of the Journal Universidad Médica Pinareña, 2014-2017 - Adrián Alejandro Vitón Castillo; Silvio Casabella Martínez; Lucia Germán Flores; Gabriel García Villacampa; Yanisleidy Bravo Malagón (Universidad Médica Pinareña, 2018)
Introduction: scientific journals are the means of excellence for the dissemination of the results of researches. Bibliometric studies allow the assessment of the scientific production of a determine journal; representing a guide for editorial teams in order to plan the strategies. Objective: to characterize the scientific production of the Journal Universidad Médica Pinareña, throughout 2014-2017. Method: bibliometric, descriptive, longitudinal and retrospective study of the scientific production published in the Journal Universidad Médica Pinareña, during 2014-2017. In this period, 82 articles were published, analyzing the totality of them. Descriptive statistics was applied; statistical measures such as absolute frequencies, relative percentages and the Price Index were used. Results: there was observed a predominance of original articles (46,34 %) and multiple authorships, where there were articles with four authors accounted for 62 %. The Associate Professors outweighed (38,57 %); 39,02 % of the articles came from Ernesto Che Guevara de la Serna School of Medical Sciences, on the other hand, 7,32 % came from Havana and Ciego de Avila institutions. The average of references per article was 14,3 % and the Price Index of 0,76 %. Conclusions: the Journal Universidad Médica Pinareña has a demanding editorial process, publishing state of the art articles. The original articles represent the greatest contribution to knowledge development. The faculties of medical sciences and provincial hospitals contribute the largest number of investigations to the journal.